2018
DOI: 10.1371/journal.pbio.2006062
|View full text |Cite
|
Sign up to set email alerts
|

Repeated translocation of a gene cassette drives sex-chromosome turnover in strawberries

Abstract: Turnovers of sex-determining systems represent important diversifying forces across eukaryotes. Shifts in sex chromosomes—but conservation of the master sex-determining genes—characterize distantly related animal lineages. Yet in plants, in which separate sexes have evolved repeatedly and sex chromosomes are typically homomorphic, we do not know whether such translocations drive sex-chromosome turnovers within closely related taxonomic groups. This phenomenon can only be demonstrated by identifying sex-associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 96 publications
5
94
0
Order By: Relevance
“…Movement of the sex-determining region can cause once-differentiated sex chromosomes to become similar again (Rovatsos et al 2019). Alternatively, translocation and could enhance adaptation through capture and subsequent sex-linkage of genes (Tennessen et al 2018). The male-specific haplotypes we identified on Ots17 span overlapping regions of 15 Mb and 20 Mb of the 22 Mb chromosome and contain 481 genes, based on the Chinook salmon genome assembly annotation (Christensen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Movement of the sex-determining region can cause once-differentiated sex chromosomes to become similar again (Rovatsos et al 2019). Alternatively, translocation and could enhance adaptation through capture and subsequent sex-linkage of genes (Tennessen et al 2018). The male-specific haplotypes we identified on Ots17 span overlapping regions of 15 Mb and 20 Mb of the 22 Mb chromosome and contain 481 genes, based on the Chinook salmon genome assembly annotation (Christensen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, whilst it was initially shown that organisms with a long haploid phase exhibit lower levels of sex chromosome divergence, including some algae (Ahmed et al, 2014) and plants (Bergero, Qiu, & Charlesworth, 2015;Chibalina & Filatov, 2011), a recent study using a larger data set of sex-linked genes found rapid degeneration of the Silene latifolia Y chromosome (Papadopulos, Chester, Ridout, & Filatov, 2015). This result, together with the observation that many plant clades exhibit turnover of sex chromosome systems (Balounova et al, 2019;Charlesworth, 2015;Martin et al, 2019;Moore, Harkess, & Weingartner, 2016;Tennessen et al, 2018), suggest that haploid selection might have a minimal effect on rates of Y degeneration.…”
Section: Accumulation Of Deleterious Mutationsmentioning
confidence: 98%
“…In addition to turnover in the chromosome pair recruited to determine sex, transitions between different sex chromosome systems (e.g., XY to ZW, or ZW to XY) are also well documented across numerous clades. This diversity is particularly pronounced in certain groups of reptiles (Gamble et al, ; Pokorná & Kratochvíl, ), amphibians (Jeffries et al, ), fish (Darolti et al, ; Kitano & Peichel, ; Mank, Promislow, & Avise, ), insects (Blackmon & Demuth, ; Vicoso & Bachtrog, ) and plants (Balounova et al, ; Martin et al, ; Tennessen et al, ), where turnover between male (XY) and female (ZW) heterogamety is common over relatively short evolutionary time periods (Pennell et al, ). While recent efforts, including those of the Tree of Sex Consortium, have focused on characterizing the tremendous diversity of sex chromosomes across species, it is clear that we currently have an incomplete understanding of the variation in sex determination mechanisms across the tree of life (Bachtrog et al, ; Tree of Sex Consortium, ).…”
Section: Introductionmentioning
confidence: 99%
“…The shared MSY locus therefore suggests a single origin of dioecy in Nepenthes that most likely predates the most recent common ancestor of extant Nepenthes at 17.7 (CI 11.0–24.3) million years ago but followed the split between Nepenthaceae and hermaphroditic Droseraceae at least 44.2 million years ago (average 71.1 with CI 44.2–98.0; Text ). However, the age of the shared MSY core does not necessarily reflect the age of the sex chromosomes: their identity could have changed over time and may also differ between Nepenthes species because the ancestral MSY could have been translocated to other chromosomes in a process called “sex‐chromosome turnover” (Blaser et al ; Jeffries et al ; Tennessen et al ). Nevertheless, the Nepenthes MSY core is probably older than the heteromorphic S. latifolia sex chromosomes (∼11 million years, Krasovec et al ).…”
Section: Discussionmentioning
confidence: 99%
“…First, an MSY may contain sequences that are absent from the X, and thus male specific (Y‐hemizygous, transmitted only from fathers to sons). As X and Y chromosomes are thought to evolve from a pair of autosomes, the gain of male‐specific sequences can be explained by several mechanisms, such as the rise of a new male‐determining mutation, or the translocation of a male‐determining cassette (Tennessen et al ), or the localized expansion of repetitive sequences due to the lack of recombination. Second, over evolutionary time, the MSY may undergo genetic degeneration and lose functional genes that were initially shared with the X chromosome (Bachtrog ).…”
mentioning
confidence: 99%